The Epidemiology of Hospital-Referred Head Injury in Ardabil City - Esmaeil Farzaneh; Ghasem Fattahzadeh-Ardalani; Vahid Abbasi; Fariba Kahnamouei-aghdam; Behnam Molaei; Elham Iziy; Habib Ojaghi (Emergency Medicine International)
Background and Purpose. Trauma is the leading cause of death for youth in developing countries. Given the prevalence of head trauma (HT) in society and its complication and burden, the epidemiologic study of head trauma is necessary and is the main aim of this study. Materials and Methods. This retrospective population-based survey describes the epidemiology of head injury in a defined population in Ardabil city. It includes all 204 patients with head injury referred to the University Hospital of Ardabil, Iran, during 2013-2014. Data were collected by a checklist and analyzed by statistical methods in SPSS.19. Significance level p<0.05 was considered. Results. Of all registered cases, 146 (71.6%) were male and the rest of them were female. Most of HT patients lived in Ardabil city (60.8%). The mean age of patients was 22.6 ± 25.9 and most of victims were young. 24.5% of traumatic patients have injuries in severe to critical level (grade 3-4). The most cause of trauma was accidents (41.7%). Most of injuries occurred in night (55.9%) and in summer season (42.2%). Causes were traffic accident in 41.7%. Conclusion. Results showed that the leading cause of head trauma especially in the warm seasons is accidents and so, designing programs to reduce road accidents can dramatically reduce the rate of trauma in the future in Ardabil province.